(untitled) (Eurasian Journal of Philology Science and Education, 2018)
It is known that the recording of the versions of the legend «Alpamys Batyr» and its first research started already in the last quarter of the nineteenth century. Its various different variants, were several times published by Jusipbek Shahislamov, not to mention other researchers. The study of this epic heritage was carried out by well-known scientists of the Soviet Union. Their works were focused on the typology of genre of the legend «Alpamys Batyr». Comparing variants of wide circulation in the Uzbek, Karakalpak and Kazakh traditions, they stopped especially on the main features of each version. The earliest known to us versions of the legend «Alpamys Batyr» can be found in the works of Maykot and Zhiemurat. The researcher gives sspecial attention to differences between these options. There it is also reported about the version published by S.Mukanov. The article also highlights historical issues related to the problem of the legend.